"Cross Paths": Once Again About the Relevance of a Combined Medical and Psychological Approach to a Person as a Client and a Patient at the Same Time - Alexander Kocharian; Nataliia Barinova (Психологічне консультування i психотерапія)
The article is devoted to rethinking the functions, duties and vectors of directing the efforts of practicing psychologists in the situation of psychological assistance to specific people suffering from hostilities, shelling, martial law, general traumatization caused by the military conflict. It is emphasized that the general circumstances of today put forward new requirements in the field of providing psychological services to the population. Their distinguishing feature is the impossibility of separating the actual psychological, medical, socio-economic and legal issues, although the specified aspects definitely have their own specifics. The difficulties with regard to the specific mental state of a person who turns to a psychologist or a family doctor are that it is often impossible to separate disorders of the somatic, mental or personal spectrum, so to speak, in their pure form. And only instrumental and laboratory tests, as well as psychodiagnostics, which objectify the complaints and/or requests of a person about bad health, can determine the defining aspect of the efforts of the relevant specialist (doctor, psychologist or social worker). It is emphasized that corrections should be introduced in the retraining of both psychologists and medical workers belonging to the primary health care sector, namely: in the retraining of psychologists, more attention should be paid to the medical aspects of understanding the course of stress, PTSD, altered emotional states, and personality pathology, somatogenic, etc. Instead, during the retraining of medical workers and doctors, it is necessary to strengthen the psychological nuances of understanding the experience of anxiety, emotional trauma, acute emotional reactions, the specifics of the action of protective mechanisms, etc. Only a comprehensive medical and psychological approach can optimally provide effective assistance to a person who has suffered in a traumatic situation. Unlike doctors, a psychologist-practitioner is not armed with clear protocols of actions in the situation of providing first-line psychological assistance. That is why it is necessary to develop indicative standards for determining the priority of providing psychological or medical services to a specific person in specific circumstances. At the same time, when choosing a consulting-psychotherapeutic paradigm, it is client-centered therapy that can be considered as a principled strategy that "unlocks" the hidden, implicit problems of client-patients, ensuring proper understanding by them and an appropriate attitude to both somatic, mental, and somatoform problems. , and somatogenic disorders. The latter creates the necessary compliance of the patient/client with the medical doctor and psychologist.